2017
DOI: 10.1161/jaha.117.006290
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in Trajectories of Hospitalization in US Men and Women With Heart Failure

Abstract: BackgroundPrior studies have documented racial and ethnic disparities in hospitalization among patients with heart failure (HF). However, racial/ethnic differences in trajectories of hospitalization following the diagnosis of HF have not been well characterized. This study examined racial/ethnic differences in individual‐level trajectories of hospitalization in older adults with diagnosed HF.Methods and ResultsData from a nationally representative prospective cohort of US men and women aged 45 years and older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Data from the Health and Retirement Study from 1998 to 2014 show racial and ethnic differences in hospitalization trajectories over 24 months after HF diagnosis. 87 Compared with NH males, Hispanic males have declines in hospitalization rates after initial diagnosis (Hispanic×time, −0.52 [95% CI, −0.99 to −0.05]) but increases in hospitalizations in later stages of disease (Hispanic×time 2 , 0.06 [95% CI, 0.00–0.12]). Among females, Black individuals had significantly more hospitalizations throughout the follow-up period compared with other groups (5.8 total hospitalizations in Black individuals versus 4.7 in White individuals versus 4.7 in Hispanic individuals; unadjusted P for ANOVA across all race groups <0.001).…”
Section: Cardiomyopathy and Heart Failurementioning
confidence: 99%
“…Data from the Health and Retirement Study from 1998 to 2014 show racial and ethnic differences in hospitalization trajectories over 24 months after HF diagnosis. 87 Compared with NH males, Hispanic males have declines in hospitalization rates after initial diagnosis (Hispanic×time, −0.52 [95% CI, −0.99 to −0.05]) but increases in hospitalizations in later stages of disease (Hispanic×time 2 , 0.06 [95% CI, 0.00–0.12]). Among females, Black individuals had significantly more hospitalizations throughout the follow-up period compared with other groups (5.8 total hospitalizations in Black individuals versus 4.7 in White individuals versus 4.7 in Hispanic individuals; unadjusted P for ANOVA across all race groups <0.001).…”
Section: Cardiomyopathy and Heart Failurementioning
confidence: 99%
“…Atherosclerotic cardiovascular disease (ASCVD) remains the leading cause of morbidity and mortality globally, particularly in people with type 2 diabetes. [1][2][3] In the general US population, studies have reported persistent racial and ethnic differences in cardiovascular morbidity and mortality, 4,5 with the higher prevalence of cardiometabolic risk factors reflecting the earlier age of onset of cardiovascular diseases among black people compared to white people. 6,7 However, among people with diabetes, there is conflicting evidence about whether black people have an increased risk of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Black women in our cohort were particularly less likely to be eligible for advanced therapies, and since they more frequently identified non‐spousal caregivers, it is possible that implicit bias may have been present during our evaluation process. Black patients being evaluated for advanced HF therapies may not necessarily fit a “traditional” family framework, as Black individuals are less likely to be married compared to other race‐ethnic groups, and may be more likely to rely on help from multiple family members including those outside of the home 22,23 . As Black patients often present at a later stage of illness than non‐Black patients, providers’ assumptions regarding increased requirements of social support, combined with a non‐traditional family support plan, may disadvantage Black patients undergoing evaluation.…”
Section: Discussionmentioning
confidence: 99%